RESILIENSI PEREMPUAN DENGAN KEHAMILAN TIDAK DIINGINKAN DI KOTA BANDUNG - Jean Klara Paliyama; Ellya Susilowati; Eni Rahayuningsih (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
Resilience is a person's ability to survive, rise, and adapt to difficult conditions. This study aims to examine the resilience of women with unwanted pregnancies at the Hope Growing House Foundation, Bandung City, West Java. The aspects studied include 1) Informant Characteristics 2) Emotion Regulation 3) Impulse Control 4) Analysis of Causes of Problems 5) Reaching Out. This study uses a descriptive qualitative approach to three informants JR, L, ENS and one social worker namely ADK. Data collection techniques used in-depth interviews, observation and documentation studies.The results showed that the informants had less resilience due to unwanted pregnancy. The aspect of resilience that is lacking is emotional regulation where at the beginning of pregnancy the informant thought to commit suicide and in the aspect of impulse control the informant experienced trauma. To overcome this, the researcher designed a